Comparison of clinical application of locking plate versus cancellous screw in structural autologous bone grafting during TKA for medial tibial bone defects - Ma, Nanshan; Cheng, Yiwei; Ding, Haoyuan; Han, Dapeng; Zhong, Sheng; Xie, Jun; Xia, Qing; Zhang, Jing; Xin, Pengfei; Xiao, Lianbo (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveTo compare the clinical outcomes of locking plate versus cancellous screw fixation in structural autologous bone grafting for medial tibial bone defects during total knee arthroplasty.MethodsA retrospective analysis was conducted on 66 patients with medial tibial bone defects who underwent TKA between January 2024 and December 2024. Among them, 34 patients received locking plate fixation (LP group), and 32 patients received cancellous screw fixation (CS group). Postoperative outcomes, including the hip–knee–ankle (HKA), Knee Society Score (KSS) and postoperative complications were recorded and compared to evaluate graft integration and functional recovery.ResultsAll patients successfully completed the surgery. At the final follow-up, both groups showed significant improvement in HKA angle, KSS Knee Score, and KSS Function Score compared to preoperative values (P < 0.05). However, no statistically significant differences were observed between the two groups at any time point in terms of KSS Knee and Function Scores (P > 0.05). No postoperative complications occurred in either group during the follow-up period.ConclusionCompared with conventional cancellous screw fixation, the use of locking plate combined with structural autologous bone grafting provides similarly favorable clinical outcomes. Furthermore, locking plate offer broader intraoperative applicability and may serve as an effective internal fixation strategy for managing medial tibial bone defects during TKA.